La metodología del entrenamiento y su incidencia en la técnica del pase con el pie en los niños de la categoría sub-9 de fútbol de la Escuela Deportiva Municipal del Cantón Babahoyo, Provincia de los Ríos en el año 2016 - Cerón Mindiola, Mario Enrrique (2016)
The thesis entitled "The methodology of training and its incidence in the foot-pass technique in the children of the sub-9 soccer category of the municipal sports school of Babahoyo canton, province of Los Ríos in 2016" unveils the Current situation presented by football coaches of the institution referred to, in order to meet the objectives, methods were selected from the theoretical and empirical levels of scientific research, using mathematical and statistical methods for the purpose of processing and validate The results obtained. The shortcomings observed in the visits to ten training sessions served as a basis for the determination of the elements that a Model must contain to support the training system for the development of the technical condition of children in the sub-9 category, That transit through the school categories. We believe that the use of the proposed elements, as a basis for the elaboration of the model, can contribute to raising the scientific level of coaches to face the pedagogical direction of the training process aimed at developing the technical skills of their athletes